Genetic variation at the synaptic vesicle gene SV2A is associated with schizophrenia - Mattheisen, Manuel; Strohmaier, Jana; Treutlein, Jens; Meier, Sandra Melanie; Witt, Stephanie; Rietschel, Marcella (Schizophrenia research, 2012)
Convergent evidence from pharmacological and animal studies suggests a possible role for the synaptic vesicle glycoprotein 2A gene (SV2A) in schizophrenia susceptibility. To test systematically all common variants in the SV2A gene region for an association with schizophrenia, we used a HapMap-based haplotype tagging approach and tested five SNPs in 794 patients and 843 controls. The SNP rs15931 showed evidence for an association with schizophrenia and was followed-up in an independent sample of 2581 individuals (overall p-value=0.0042, OR=0.779). Our study in the German population provides evidence, at a genetic level, for the involvement of the SV2A gene region in schizophrenia.